The impact of official development assistance on foreign direct investment: the case of Japanese firms in India - Ono, Saori; Sekiyama, Takashi (Frontiers in Political Science, 2024)
While there is no clear answer to the overall impact of Official Development Assistance (ODA) on Foreign Direct Investment (FDI), it has been pointed out that Japanese ODA promotes its FDI. However, the mechanism of ODA's impact on FDI has not been fully examined at the micro level, as most previous studies have used macro-level data. Therefore, this study examines the impact of ODA on FDI at the micro level in India, where an increase in ODA and FDI from Japan have been observed in recent years. Interviews were conducted with three Japanese firms and five Japanese public organizations, while questionnaires were administered to thirty-three Japanese firms. The results reveal that ODA effectively promotes FDI, albeit to a lesser extent than other FDI determinants. Economic infrastructure development through ODA, the expectations of such development, and the reception of orders for ODA Loan projects, promote FDI. Furthermore, the role of public institutions, including providing information to firms and acting as intermediaries with the government, is more effective in promoting FDI than ODA. The novelty of this study lies in its clarification of the mechanism through which ODA promotes FDI from a micro-perspective, as revealed by a questionnaire survey conducted among firms. The FDI-promoting effects of ODA for economic infrastructure and ODA Loan suggested in this study not only contributes to the academic community but also have important implications for ODA policymakers.